2015
DOI: 10.1039/c4ra15443f
|View full text |Cite
|
Sign up to set email alerts
|

Implications of sample aging on the formation of internally etched silica coated gold nanoparticles

Abstract: Local refractive index sensitivity modelling using the plasmonic properties of gold nanospheres assists in the elucidation of the nanoparticle-rattle formation as a function of sample age and storage conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…An intermediate case is observed for GNR-Si23, with approximately half of them well-isolated and the other half showing some degree of degradation. Interestingly, it has been reported that silica shell etching is not homogeneous, occurring preferentially in the inner layers of silica, while outer layers are more resistant to etching. , This selective etching was also observed in GNR-Si23 and GNR-Si35 (Supporting Information, Figure S3), and it would explain why, even if silica shells are partially degraded, they do not lose their capacity to confer steric hindrance to GNRs.…”
Section: Resultsmentioning
confidence: 67%
“…An intermediate case is observed for GNR-Si23, with approximately half of them well-isolated and the other half showing some degree of degradation. Interestingly, it has been reported that silica shell etching is not homogeneous, occurring preferentially in the inner layers of silica, while outer layers are more resistant to etching. , This selective etching was also observed in GNR-Si23 and GNR-Si35 (Supporting Information, Figure S3), and it would explain why, even if silica shells are partially degraded, they do not lose their capacity to confer steric hindrance to GNRs.…”
Section: Resultsmentioning
confidence: 67%
“…The 1/e decay length is approximated as ~4 nm, which is reasonable assuming each branch can be treated as a nanorod [34]. The effective refractive index of the SAM can be estimated from where these lines cross [50]. As a result, the effective refractive index of the SAM is 1.43 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic electromagnetic field decay length ( l d ) for Ag@Au nanoparticles was determined using LSPR and the following model: where Δλ max is the LSPR wavelength shift, m 1 is the linear refractive index sensitivity, m 2 is a nonlinear refractive index sensitivity term that accounts for nonlinearity in the local electric field, n silica and n water are the effective refractive indices of silica and the bulk solution, respectively, and t is the silica membrane thickness. To determine these values, Ag@Au and Ag@Au@SiO 2 nanoparticles were incubated in 0–60% (w/v) sucrose solutions, and LSPR spectra were collected.…”
Section: Methodsmentioning
confidence: 99%